Legal analysis of Niet Onvankelijke Verklard's Decision (NO) on the application for announcement of marriage a TNI soldier who forged a marriage license (Case Study of Cilacap Religious Court Decision Number: 0922/Pdt.G/2021/PA.Clp) - Hamid Hamid (Goodwood Publishing, 2024)
Purpose: This study aims to analyze the application of law to the administrative requirements of a Marriage License (SIN) that is formally flawed and the implications of the Niet Onvankelijke Verklaard (NO) decision on the marriage of a TNI soldier who falsified the Marriage License (SIN). Research methodology: The method in this study is written in a Normative Juridical manner, is descriptive analytical, the legal material is with secondary data that includes related laws and books. Results: The results of the study state that the application of the provisions in Article 72 paragraph (2) of the Compilation of Islamic Law which regulates the provisions for the annulment of a marriage carried out with the condition of